Diagnostic Accuracy of CA-125 Levels for Ovarian Tumor Patients with Suspected Malignancy - Pangaribuan, Machyuddin Tumpak Marojahan; Razali, Renardy Reza; Darmawi, Darmawi (http://dharmais.co.id/, 2025)
Background: Ovarian cancer is a deadly gynecological cancer that appears in ovarian tissue. To detect earlier stages of ovarian cancer and prevent unnecessary surgery, an examination and screening strategy with higher sensitivity and specificity levels are needed. The CA-125 examination is available at Arifin Achmad Hospital and has often been performed on ovarian tumor patients with suspected malignancy. Currently, the accuracy of the CA-125 examination still raises debate in diagnosing malignant ovarian tumors. This study aims to determine the diagnostic accuracy of CA-125 levels in diagnosing ovarian cancer in ovarian tumor patients with suspected malignancy at Arifin Achmad Hospital. Method: This research is an analytical diagnostic test study with a cross-sectional approach, using secondary data recorded from medical records from 2019 to 2022 on ovarian tumor patients with suspected malignancy at Arifin Achmad Regional Hospital.Results: The diagnostic accuracy of CA-125 levels in ovarian cancer is 94.5%, the optimal cut-off value is 36.5 IU/ml, the sensitivity is 86.1%, the specificity is 90.1%, the positive predictive value is 89.4%, the negative predictive value 86.9%. The results of the study showed that there was a significant age difference between benign ovarian tumors and ovarian cancer. The most common histopathological feature of benign ovarian tumors is serous cystadenoma. The most common histopathological feature of malignant ovarian tumors is serous adenocarcinoma. There is a significant relationship between CA-125 levels and ovarian tumors.Conclusion: The identification of CA-125 levels in diagnosing ovarian cancer in ovarian tumor patients with suspected malignancy was a promising test with high diagnostic accuracy level